PENGARUH MODEL KOOPERATIF TIPE KARTU ARISAN PADA MATERI SEL TERHADAP HASIL BELAJAR SISWA KELAS XI SMA - Rahmawati, Rina; Aryati, Eka; Yokhebed, Yokhebed (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research aimed to identify the effect of cooperative learning type of kartu arisan toward students learning outcomes. The research focused on the material about cell for eleventh grade science major. The research applied quasi-experimental method with non-equivalent control group design. Sample in this research was taken through intact group technique, where eleventh grade of science 1 as the experimental class and eleventh grade of science 2 as the control class. The instrument was a multiple-choice test consisting of 25 questions. The average value of students outcomes at the experimental class was 19.97. Meanwhile, the average for control class was 18.38. Using U Mann-Whitney test, the research obtained -Zcount < -Ztable there was -1.98 < -1.96. This value means that there is a significant difference of learning outcomes between students who use cooperative learning type of arisan card and those who study conventionally. The value of effect size obtained in this research was 0.45 which could be classified medium. It shows us that cooperative learning of type arisan card has an effect as much as 17.36% towards students outcomes, especially in the material of cell eleventh grade science student. Keywords: Cooperative Learning type of kartu arisan, learning outcomes, cell